Malaria Risk Analysis on Stunting Incidence in Toddlers - Marlin Mayling Jarona; Ellen R.V Purba; Lilys Irianty Natalia Purba (Indonesian Journal of Global Health Research, 2025)
Papua recorded the highest number of malaria cases in Indonesia in 2021, with 275,243 individuals affected. Keerom Regency ranked second with 17,901 cases in 2020. Recurrent malaria infections in toddlers can lead to chronic nutritional disorders, anemia, and immune system impairments, which disrupt growth and increase the risk of stunting. Objective: To analyze the risk of malaria on stunting incidence among toddlers based on gender, age, history of fever, maternal knowledge, and malaria prevention practices in Keerom Regency. Method: This was a quantitative analytic study with a cross-sectional design. The study population consisted of toddlers aged 0–59 months who lived in Keerom Regency and had been diagnosed with clinical malaria, with or without stunting. A purposive sampling technique was applied. Data were collected through structured interviews using validated questionnaires administered to mothers, and anthropometric measurements of toddlers were taken to determine nutritional status based on height-for-age indicators. Data were analyzed using the chi-square test. Results: Showed that a history of fever, maternal knowledge of breastfeeding and supplemental feeding, and malaria prevention practices were significantly associated with stunting (p<0.05). Conclusions: Children with fever had a 90.6% stunting rate. Improving maternal knowledge and malaria prevention is essential to reduce stunting.